PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Studi pada PT SWEET INDOLAMPUNG) - Muhammad Bulhanudin; Ahyar Yuniawan (Faculty of Economics and Business Diponegoro University, 2018)
Human resources play an important role in a company since human is the determiner of the company. Company’s success is measured by the performance of employees. High employee performance makes the success of the company is also getting higher. The purpose of this study is to analyze the influence of transformational leadership and compensation satisfaction on organizational commitment and the effect on employee performance. The population in this study were employees of PT Sweet Indolampung. This study was conducted by distributing questionnaires to a sample of 300 employee using simple random sampling techniques. Data analysis method used is multiple linear regression analysis. Mechanical testing data used this study include the path analysis and sobel test to test the effect of mediation. The result showed that transformational leadership positive and significant influence to organizational commitment, compensation satisfaction positive and significant influence to organizational commitment, transformational leadership positive and significant influence to employee performance, compensation satisfaction positive and significant influence to employee performance, and organizational commitment positive and significant influence to employee performance